Influence of Electronic Procurement Systems on Performance of National Hospital Insurance Fund in Selected Counties in Kenya - Opondo, Patrick Barasa (JOOUST, 2019)
Operations management department in government parastatals is a crucial division. In the business world today, the supplies community is targeting the 'big' organizations and in particular government parastatals which make large purchases of both services and goods. Some organizations have implemented e-procurement technologies and succeed whereas others have failed to adopt the system after implementation with devastating consequences. E-procurement refers to use of internet-based systems to carry out procurement processes including research, sourcing, negotiations, ordering, receipts and post purchase reviews. In Kenya, procurement functions have been characterized by lack of professionalism resulting to unethical practices. The main theory driving this study was the resource-based theory which suggests strategic resource-management framework as a source of competitive advantage for a firm. Therefore, this study sought to establish the influence of electronic procurement on performance of National Hospital Insurance Fund (NHIF). Specific objectives were: to investigate the influence of information technology on performance of NHIF, to determine the influence of government policies on performance of NHIF and to examine the influence of financial resources on performance of NHIF. The study targeted 154 employees and a sample size of 57 employees filled the questionnaires. Multiple regression was used to investigate the influence of the independent variables on the dependent variable basing on covariance. Analysis of responses t open ended questions also aided in making conclusions. Results revealed that information technology has positive and significant influence on performance (~ = 0.529; p<.05), government policies had a positive influence on performance (~= 0.480; p<.05) and financial resources positively and significantly influences performance (~= 0.575; p<.05). The study provides valuable information to the management of National Hospital Insurance fund who shall be able to develop interventions on information and communication technology, Finance and Government policies to facilitate e-procurement in the organization thus ensuring proper administration and appreciation. Management will also be able to facilitate the integration of the procurement system in various department of the organization.